O mentoring como processo de transferência de conhecimento: estudo experimental a partir de reformados e desempregados qualificados - Moura, R. D.; Dias, Á.; Quintas, C.; Costa, D. (International Journal on Working Conditions, 2015)
The study was based on the development of a methodological framework applied experientially during the research. The goal was to transfer to active employee’s retired knowledge or long-term unemployed. A double main objective was defined: boosting labor market maximizing the explicit and tacit knowledge held by those officials; contribute to the competitiveness of the economy and provide new experiences to the people involved. The methodology applied in a business context had several steps: (a) identify the explicit and tacit knowledge of the said officials; (b) access to persons holding knowledge; (c) integrate knowledge in mobilizing projects in companies; (d) combining ideas and initiatives, (e) refine the identified knowledge; (f) strengthen and apply knowledge. Points (a) and (b) were supported by an IT platform that included an interactive forum. Step (c) defined the mobilizing projects. The steps (c) through (f) is supported in a mentoring program with eight components: mission; focus; goals; initiatives; inputs; production; outputs; impacts. It was concluded that the tutorials agents agreed to new learning; companies incorporated new knowledge and more competitiveness; the mobilizing projects must be developed in the medium and long term; measure the actual effects of knowledge transfer and deliver the expected returns.